2020
DOI: 10.1097/ypg.0000000000000270
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the role of gut microbiota in the pathogenesis of schizophrenia

Abstract: Schizophrenia is a chronic mental disorder with marked symptoms of hallucination, delusion, and impaired cognitive behaviors. Although multidimensional factors have been associated with the development of schizophrenia, the principal cause of the disorder remains debatable. Microbiome involvement in the etiology of schizophrenia has been widely researched due to the advancement in sequencing technologies. This review describes the contribution of the gut microbiome in the development of schizophrenia that is f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 124 publications
0
6
0
Order By: Relevance
“…[49][50][51] The gut microbiome has been linked to the development and maintenance of schizophrenia, [52] This association has been a prominent trend in schizophrenia research for the past 50 years, [53] primarily due to advances in sequencing methods. [54] A recent systematic review revealed that schizophrenia often exhibits higher levels of Prevotella and lower levels of Haemophilus, Bacteroides, and Streptococcus. [55] These gut microbes could be involved in the pathogenesis of schizophrenia by causing or exacerbating neuroinflammation due to gut dysbiosis.…”
Section: Gut Microbiota and Schizophreniamentioning
confidence: 99%
See 1 more Smart Citation
“…[49][50][51] The gut microbiome has been linked to the development and maintenance of schizophrenia, [52] This association has been a prominent trend in schizophrenia research for the past 50 years, [53] primarily due to advances in sequencing methods. [54] A recent systematic review revealed that schizophrenia often exhibits higher levels of Prevotella and lower levels of Haemophilus, Bacteroides, and Streptococcus. [55] These gut microbes could be involved in the pathogenesis of schizophrenia by causing or exacerbating neuroinflammation due to gut dysbiosis.…”
Section: Gut Microbiota and Schizophreniamentioning
confidence: 99%
“…A brief introduction Schizophrenia is a significant cause of disability with varied causes, and gut microbiome has been linked to its development [45][46][47][48][49][50] Depression is a prevalent cause of disability worldwide, with the gut microbiome being implicated in its pathogenesis [60][61][62] Generalized anxiety disorder (GAD) is a prevalent and enduring type of anxiety, affecting 4%-6% of the total population [70] Autism spectrum disorder (ASD) is a neurodevelopmental condition that affects social interaction and communication and is typically identified in early childhood [1,5,77,78] Neurotransmitters involved in the mental disorders Impairment in the tryptophan to serotonin conversion pathway is plausibly linked to schizophrenia [9] Researchers suggest that d-serine could be associated with schizophrenia [54,57] The role of GABAergic transmission in schizophrenia has recently risen in significance [54] Tryptophan and Serotonin are centrally involved in the pathogenesis of depression [9] Modifying dopamine levels may have therapeutic applications for depression [21] GABA has been associated with treating depression [31] Glutamatergic signaling has been linked to depression [42,44] Tryptophan and serotonin also play a crucial role in the pathogenesis of anxiety [9] Modifying dopamine levels can have therapeutic applications for anxiety [21] GABA can also reduce anxiety [31] Modifying dopamine levels can have therapeutic applications on autism [21] Glutamate metabolization may be linked to autism [38,42] Microbiota effect on the neurotransmitters -Numerous bacterial species have reportedly expressed serotonin-synthesizing properties [14] -Gut commensal strains Lactobacillus and Bifidobacterium have been found able to produce GABA [54] -Altering gut microbial may modify the metabolism of d-amino acids…”
Section: Schizophrenia Depression Anxiety Disorder Autism Spectrum Di...mentioning
confidence: 99%
“…Furthermore, it has been proposed that d-serine may be associated with SCH; consequently, changes in the gut microbiota could modulate the metabolism of d-amino acids ( 16 , 17 ). Moreover, Lactobacillus and Bifidobacterium in the gut may be able to produce GABA, a neurotransmitter that has been shown to be associated with SCH ( 16 ).…”
Section: Gut Microbiome and Schizophreniamentioning
confidence: 99%
“…Furthermore, it has been proposed that d-serine may be associated with SCH; consequently, changes in the gut microbiota could modulate the metabolism of d-amino acids ( 16 , 17 ). Moreover, Lactobacillus and Bifidobacterium in the gut may be able to produce GABA, a neurotransmitter that has been shown to be associated with SCH ( 16 ). Within this context, alterations in the glutamate glutamine-GABA cycle and reduced levels of glutamate in the brain were proposed to be associated with NMDA receptor hypofunction in SCH ( 18 ).…”
Section: Gut Microbiome and Schizophreniamentioning
confidence: 99%
“…An imbalance within the intestinal microecological niche, referred to as dysbiosis, has been shown to constitute a risk factor for a number of pathologic conditions including ischemic stroke (Pluta et al, 2021 ), schizophrenia (Ghorbani et al, 2021 ; Samochowiec and Misiak, 2021 ), major depression (Simpson et al, 2021 ), abdominal aortic aneurysm (Tian et al, 2022 ), Takayasu arteritis (Desbois et al, 2021 ), coronary heart disease (Liu H. et al, 2020 ), and others (Hou et al, 2022 ). The intestinal microbiome affects blood vessels by means of bidirectional interactions with its endothelium and when dysbiosis occurs, and it might be associated with endothelial dysfunction through a number of mechanisms such as an increase in angiotensin-converting enzyme activity and promotion of inflammatory response as well as oxidative stress (Leslie and Annex, 2018 ).…”
Section: Cerebral Aneurysm and Intestinal Microbiomementioning
confidence: 99%